Isolation and characterization of Pseudomonas otitidis TH-N1 capable of degrading Zearalenone. (January 2015) - Tan, Hui; Zhang, Zhimin; Hu, Yanchun; Wu, Lei; Liao, Fei; He, Jie; Luo, Biao; He, Yajun; Zuo, Zhicai; Ren, Zhihua; Peng, Guangneng; Deng, Junliang
Abstract: Zearalenone (ZEA) is a nonsteroidal estrogenic mycotoxin produced by various Fusarium species and causes hyperestrogenism and related toxicosis of farm animals and humans. The present study aimed to isolate and identify ZEA-resistant bacteria from rumen in order to develop some strategies for detoxifying ZEA-contaminated food and feed. A bacterial strain was isolated from the rumen contents for its ability to utilize ZEA as the sole carbon and energy source. The isolate was an aerobic, Gram-negative, rod-shaped bacterium with single polar flagellum and was named Pseudomonas otitidis TH-N1 based on the morphology and 16S rRNA gene sequence. Meanwhile, the present study investigated that how various influence factors of P. otitidis TH-N1 could remove ZEA from a liquid medium. The optimal temperature, pH value, and concentrations of bacteria for the biodegradation of ZEA were 37 °C, 4.5, and 10 9 cfu/ml, respectively. These results suggest that P. otitidis TH-N1 is a new bacterium found from the rumen and exhibited remarkable degradation activity of ZEA. It is probably a new bacterial resource to detoxify ZEA from ZEA-contaminated food and feed. Highlights: Isolated a strain which has the capability to remove ZEA from the rumen. The strain was named as Pseudomonas otitidis TH-N1. The maximum degradation rate of Pseudomonas sp. TH-N1 for ZEA (2 μg/ml) was 79%. The optimal temperature and pH value were around 37 °C and 4.5, respectively. The optimal concentration of bacteria for biodegradation of ZEA was 10 9 cfu/ml.